The development and study of common wheat introgression lines derived from the synthetic form RS7 - R. O. Davoyan; I. V. Bebyakina; E. R. Davoyan; D. S. Mikov; Yu. S. Zubanova; D. M. Boldakov; E. D. Badaeva; I. G. Adonina; E. A. Salina; A. N. Zinchenko (Вавиловский журнал генетики и селекции)
Synthetic recombination form RS7 (BBAAUS), in which the first two genomes, A and B, originate from common wheat, and the third recombinant genome consists of Aegilops speltoides (S) and Ae. umbellulata (U) chromosomes, was obtained from crossing synthetic forms Avrodes (BBAASS) and Avrolata (BBAAUU). Resistant to leaf rust, yellow rust and powdery mildew, introgression lines have been obtained from backcrosses with the susceptible varieties of common wheat Krasnodarskaya 99, Fisht and Rostislav. PCR analysis showed the presence of amplification fragments with marker SCS421 specific for the Lr28 gene in the line 4991n17. The cytological study (С-banding and FISH) of 14 lines has revealed chromosomal modifications in 12 of them. In most cases, the lines carry translocations from Ae. speltoides, which were identified in chromosomes 1D, 2D, 3D, 2B, 4B, 5B and 7B. Also, lines with the substituted chromosomes 1S (1B), 4D (4S), 5D (5S) and 7D (7S) were identified. Lines that have genetic material from Ae. speltoides and Ae umbellulata at once were revealed. In the line 3379n14, translocations in the short arm of chromosome 7D from Ae. umbellulata and chromosomes 5BL, 1DL, 2DL from Ae. speltoides were revealed. The line 4626p16 presumably has a translocation on the long arm of chromosome 2D from Ae. umbellulata and the T7SS.7SL-7DL translocation from Ae. speltoides. The T1DS.1DL-1SL and T3DS.3DL-3SL translocations from Ae. speltoides, and T2DS.2DL-2UL and T7DL.7DS-7US from Ae. umbellulata have been obtained for the first time. These lines may carry previously unidentified disease resistance genes and, in particular, leaf rust resistance genes from Ae. speltoides and Ae. umbellulata.